Xanthogranulomatous endometritis- a rare pathological entity presenting as infertility - Dr. Ekta Rani; Dr. Vijay Suri; Dr. Jasmine Sandhu; Dr. Nikita Goel; Dr. Prabhjot Kaur (Tropical Journal of Pathology and Microbiology, 2019)
Xanthogranulomatous inflammation is a distinguished histopathological entity affecting several organs, most likely kidney and gall bladder. Only a small number of cases of xanthogranulomatous endometritis (XGE) are reported in literature so far. Microscopic examination show sheets of foamy histiocytes along with other inflammatory cells on H&E stains sections. We present a case of 31-year-old female with complaint of inability to conceive for 3 years and having history of previous 3 tubal pregnancies. Hysteroscopy examination reveals fluffy endometrium, patent bilateral fornices with normal cervical mucosa. Dilatation and curettage were done and sent for histopathological examination, and diagnosis of Xanthogranulomatous Endometritis was made. As XGE is a rare inflammatory disease, awareness of this lesion is necessary for both the gynaecologist and pathologist and should be kept in differential diagnosis in the cases of infertility.